Performance of mixed algae for treatment of slaughterhouse wastewater and microbial community analysis - Taskan, Ergin (Springer Heidelberg, 2016)
This study investigated organic matter (OM) and nutrient removal efficiency of mixed algal species from slaughterhouse wastewater (SWW) by using photo-bioreactor. For this purpose, different dilution multiples of 10, 4, and 2 were applied to the SWW, and pure wastewater was finally used for algal cultivation. OM and nutrient removal performance in an algal photo-bioreactor were severely affected by the dilution ratio. After 7 days of cultivation, the highest removal percentages of total organic carbon (TOC), total nitrogen (TN), and total phosphorus (TP) were 89.6, 70.2, and 96.2 %, respectively. Furthermore, the changes in eukaryotic algae and cyanobacterial species in the algal photo-bioreactors were investigated using polymerase chain reaction (PCR) and denaturing gradient gel electrophoresis (DGGE) techniques. The results indicated that cyanobacterial species were more efficient than eukaryotic species in removing nutrients from the SWW. This study suggests that mixed algal photo-bioreactors could be used efficiently in the treatment of SWW.
Keywords: Eukaryotic algae; Cyanobacteria; Photo-bioreactor; Slaughterhouse wastewater; Nutrient removal; Molecular techniques